The effect of an NCAA Division I wrestling season on selected physiological variables - Schultz, M. P. (1997)
This study determined the effect of a wrestling season on aerobic capacity (max VO2), anaerobic power (Wingate power test), body composition (hydrostatic weighing) and strength (bench press and leg press) for a NCAA Division I wrestling team. Fifteen varsity wrestlers, aged 18-25, participated in the preseason and postseason testing. Data were analyzed utilizing independent and paired t-tests (p<0.05). The subjects were divided into three groups: combined (all 15 wrestlers); competitive (N=8); noncompetitive (N=7). The combined group found an increase in leg press strength and all of the variables associated with anaerobic power. The competitive group found no changes for any of the selected variables. The noncompetitive group increased in three of the variables associated with anaerobic power. A comparison of the competitive and noncompetitive groups revealed no changes for any variable.